2018
DOI: 10.1002/cti2.1039
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of HLA‐E by dengue and not Zika viruses

Abstract: IntroductionThe most severe form of dengue virus (DENV) illness, dengue haemorrhagic fever, is characterised by plasma leakage and increased vascular permeability.ObjectivesGiven the critical role that endothelial cells play in the pathogenesis of DENV, we wanted to determine whether infection with DENV altered the expression of MHC class I related genes including HLA‐E.ResultsIn this study, we provide evidence that HLA‐E but not MICA/B or HLA‐G is upregulated by all four serotypes of DENV in an endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
4
6
1
Order By: Relevance
“…In this study, we used an in vitro model of co-culture to analyze the cellular and molecular events required for the control of DENV-2 infection by NK cells. We demonstrated that infection of Mo-DCs by DENV-2 induced autologous NK cells to produce IFN-γ and TNFα specifically, and did not mediate degranulation, in accordance with data previously observed with ex vivo NK cells of infected patients [12][13][14]; this is possibly explained by the upregulation of MHC class-1 molecules, and HLA-E in DENV-2 infection, confirmed herein and previously described [26,27,32]. However, we cannot exclude that the cytotoxic functions of NK cells are modulated differently in the function of the DENV serotype.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we used an in vitro model of co-culture to analyze the cellular and molecular events required for the control of DENV-2 infection by NK cells. We demonstrated that infection of Mo-DCs by DENV-2 induced autologous NK cells to produce IFN-γ and TNFα specifically, and did not mediate degranulation, in accordance with data previously observed with ex vivo NK cells of infected patients [12][13][14]; this is possibly explained by the upregulation of MHC class-1 molecules, and HLA-E in DENV-2 infection, confirmed herein and previously described [26,27,32]. However, we cannot exclude that the cytotoxic functions of NK cells are modulated differently in the function of the DENV serotype.…”
Section: Discussionsupporting
confidence: 92%
“…4A), as described previously for different flaviviruses, and unlike many other viruses that down‐regulate MHC class‐1 expression on infected cells . Concomitantly, HLA‐E expression was significantly increased in DENV‐2‐infected cells, as described . Moreover, the frequency and surface‐expression of the MHC class‐1‐related chain (MIC)‐A and MIC‐B, two ligands of NKG2D, were significantly induced in DENV‐2‐infected Mo‐DCs ( p = 0.0015), but not in bystander Mo‐DCs, when compared to non‐infected cells (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Although the mechanism underlying this phenomenon is unclear, some of these responses have been attributed to elevated HLA-E expression (28). The upregulation of HLA-E, the ligand of NKG2C, is a common feature found in viral infections, such as dengue, hantavirus, and HIV (28,45,46). The engagement of NKG2C, the signature activating receptor of CD57 + /NKG2C high NK cells, leads to polyfunctional responses characterized by degranulation of cytolytic molecules as well as TNF-α and IFN-γ release (29).…”
Section: Discussionmentioning
confidence: 99%
“…Several NK cell receptors, namely DNAM-1, NKG2D, and NKp44 have been implicated in this direct recognition of DENV-infected cells (Beltrán and López-Vergès, 2014; Petitdemange et al, 2014; Costa et al, 2017; Mathew, 2018). However, DENV may also evade the NK cell response, most notably through upregulation of HLA class I (Lobigs et al, 1996; Momburg et al, 2001; Hershkovitz et al, 2008; Glasner et al, 2017; Drews et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Viruses can evade NK cell recognition by taking advantage of these inhibitory interactions. In vitro studies have shown flaviviruses, including DENV, upregulate total HLA class I as well as HLA-E, leading to inhibition of NK cell activation (Lobigs et al, 1996; Momburg et al, 2001; Hershkovitz et al, 2008; Glasner et al, 2017; Drews et al, 2018). Immune cells, particularly monocytes, are the main targets of DENV infection in vivo (Durbin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%